Creating the canon composition, controversy, and the authority of the New Testament - Laird, Benjamin P. 1979- (InterVarsity Press, 2023)
Some questions about the New Testament are far from settled, to say nothing of misconception and confusion. In this wide-ranging yet accessible overview, Bejamin Laird offers constructive insight on matters tied to the composition, collection, and authority of the New Testament canon.